Key eco-physiological leaf traits suggest a moderate to high level of thermal tolerance of alpine plants in the Western Himalaya - Hopak, Nang Elennie; Chawla, Amit (Frontiers in Plant Physiology, 2025)
Investigating thermal tolerance is vital in understanding how plant species would respond to future global temperature increase with greater rates in alpine areas, especially in the Himalaya, a biodiversity hotspot. In this study, we investigated the leaf thermal tolerance of 52 species from the Himalayan alpine region, to assess 1) the response of alpine species to different temperatures (28°C, 33°C, 38°C, 43°C, 48°C, 53°C, and 58°C), 2) the dependence of thermal tolerance (T50) on various eco-physiological leaf traits, and 3) variation in thermal tolerance among different growth forms. We found the thermal tolerance of various species to be in the range of 44.9°C to 65.9°C, the highest in graminoids (53.8°C ± 8.2°C), followed by forbs (49.8°C ± 2.2°C) and rosettes (48.7°C ± 2.4°C). We observed a significant positive correlation between T50 and leaf traits such as leaf mass per area and leaf dry matter content. We also determined thermal safety margins (TSMs), which ranged from 20.3°C (Malva neglecta) to 40.5°C (Calamagrostis emodensis) for most of the species, with a few species under 20°C, except for Rosularia alpestris at 9.7°C. Our results suggest that alpine species from the Western Himalaya, with elevated T50 and wide TSMs, are currently within their thermal safety range and are not as susceptible to temperature rise in the near future, compared to species from tropical and subtropical eco-regions, provided these are able to modulate their leaf temperature within theired ran specifige of tolerance.